Improvement of cavity plasmon resonance in high-sensitivity MIM nanostructure with rectangular air stubs inside the hexagonal-ring resonator. (1st February 2023) - Keshizadeh, Hadi; Aghaei, Fatemeh; Bahador, Hamid; Heidarzadeh, Hamid
Abstract: In this research work, 'the cavity plasmon multi-mode resonance-based refractive index sensor with ultra-high sensitivity' is presented. The proposed sensor is the metal-insulator-metal nanostructure including the bus waveguide coupled to the hexagonal-ring resonator with rectangular air stubs. The transmittance properties, electric field profile, and magnetic field profile are investigated theoretically and numerically for three types of resonator structures by using the finite-difference time-domain method. Adding the air stubs to the ring resonator structure improves the light–matter interaction and effects of cavity plasmon resonances. Also, the combination of a hexagonal ring structure with rectangular air stubs provides a structure with unique optical properties. These optical properties significantly improve the intensity of the electromagnetic field and provide a sensor with ultra-high sensitivity and high selectivity (Δ n = 0.002). The high sensitivity of 1725.5 nm RIU −1, 344 5 nm RIU −1, and 5770 nm RIU −1 was achieved for mode 1, mode 2, and mode 3 of 6-stub resonator (case 3), respectively. The results show that case 3 enhances the maximum sensitivity by about 8% for none-stub resonator (case 1) and 91% for 2-stub resonator (case 2). The figure of merit is 30.8 RIU −1 in mode 1, 74.9 RIU −1 in mode 2, and 58.6 RIU −1 in mode 3. The presented sensor can be used as a biosensor for glucose detection.